An added value analysis of Pulu Mandoti rice agricultural commodities at farmers level. Issue 1 (April 2020) - Amrullah, A; Tenriawaru, A N; Viantika, N M; Darma, R; Heliawaty,; Akib, M N
Abstract: Pulu Mandoti rice is a local rice variety that has high economic value. This rice is phenomenal because it can only grow in two villages, one of which is Salukanan Village, Enrekang Regency. Having a distinctive aroma, texture, and taste makes the demand for rice even higher in the market also to foreign countries. The high demand for pulu mandoti has an impact on the selling price of these commodities to affect the income and profits of farmers. This research aims to analyze the added value of pulu mandoti to farmers who cultivate them. This research was conducted in Salukanan Village, Baraka Subdistrict, Enrekang Regency, South Sulawesi Province, by using value-added calculations using the Hayami Method. Sampling was done by simple random sampling, with a total sample of 39 respondent farmers. The results showed that the added value of IDR 2, 851, 414, with a profit rate of 90.27%.